Race and the Chilean miracle : neoliberalism, democracy, and Indigenous rights - Richards, Patricia, 1971- (Pitt Latin American series., 2013)
The economic reforms imposed by Augusto Pinochet’s regime (1973–1990) are often credited with transforming Chile into a global economy and setting the stage for a peaceful transition to democracy, individual liberty, and the recognition of cultural diversity. The famed economist Milton Friedman would later describe the transition as the “Miracle of Chile.” Yet, as the author reveals in this book, beneath this veneer of progress lies a reality of social conflict and inequity that has been perpetuated by many of the same neoliberal programs. Here, the author examines conflicts between Mapuche Indigenous people and state and private actors over natural resources, territorial claims, and collective rights in the Araucanía region. Through ground-level fieldwork, extensive interviews with local Mapuche and Chileans, and analysis of contemporary race and governance theory, the author exposes the ways that local, regional, and transnational realities are shaped by systemic racism in the context of neoliberal multiculturalism.